Bordetella pertussis expresses a functional type III secretion system that subverts protective innate and adaptive immune responses. - MILLS, KINGSTON; ROSS, PADRAIG JOHN (American Society for Microbiology, 2008)
Certain bacteria use a type III secretion system (TTSS) to deliver effector proteins that interfere with cell function into host cells. While transcription of genes encoding TTSS components has been demonstrated, studies to date have failed to identify TTSS effector proteins in Bordetella pertussis. Here we present the first evidence of a functionally active TTSS in B. pertussis. Three known TTSS effectors, Bsp22, BopN, and BopD, were identified as TTSS substrates in B. pertussis 12743. We found expression of Bsp22 in a significant proportion of clinical isolates but not in common laboratory-adapted strains of B. pertussis. We generated a TTSS mutant of B. pertussis 12743 and showed that it induced significantly lower respiratory tract colonization in mice than the wild-type bacteria. Respiratory infection of mice with the mutant bacteria induced significantly greater innate proinflammatory cytokine production in the lungs soon after challenge, and this correlated with significantly higher antigen-specific interleukin-17, gamma interferon, and immunoglobulin G responses later in infection. Our findings suggest that the TTSS subverts innate and adaptive immune responses during infection of the lungs and may be a functionally important virulence factor for B. pertussis infection of humans.
PUBLISHED
Keywords: Biochemistry